Effectiveness of Counting Box Learning Media to Improve the Ability to Sum Numbers 1-10 for Children with Cerebral Palsy - Varel Muhammad Rizky; Nurhastuti Nurhastuti; Mega Iswari; Arisul Mahdi (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to improve the ability to add numbers 1-10 for cerebral palsy children at SD IT Permata Kita Padang by used Counting Box Learning media. Learning Media Counting Box serves as a learning prop that can be seen and makes it easier for students to count. This research uses a quantitative approach with experimental methods, namely Single Subject Research (SSR) and A1-B-A2 Design, and the data is analyzed using visual graphs by entering data in graphs which are then analyzed based on conditions A1-B-A2 The results of research used Counting Box Learning media can improve the ability to add numbers 1-10 for cerebral palsy children at SD IT Permata Kita Padang.